Carla Lonzi och krisens kritik 1969-1970 - Sandström, Frida (K&K - Kultur og Klasse, 2024)
Departing from the Italian critic, art historian, and feminist Carla Lonzi’s essay ”La critica è potere” (Critique is power) from 1970, this article discusses a crisis immanent to the concepts of art and history that dominated the late 1960s Italy. In line with Lonzi’s argumentation, this crisis resulted in what the communist Massimo Cacciari described as ”negative thinking” in 1969, and what Lonzi in her essay describes as a ”critique of the crisis”. Beyond a universal consciousness and its presupposed identities, as they were reproduced within the party form and at academic institutions during this period, artists, workers, and intellectuals turned away from formal organization, and to informal, collective practices. The separatist, decentralized and anti-authoritarian network Rivolta Femminile, founded by Lonzi in 1970, show how the subjects of crisis and critique emerge from a patriarchal and colonial regime of sexual repression.